Evaluation of the Electric Field Induced in Transcranial Magnetic Stimulation Operators - Bottauscio, Oriano; Zucca, Mauro; Chiampi, Mario; Zilberti, Luca (IEEE transactions on magnetics, 2016)
This paper aims at investigating the exposure experienced by the nursing staff executing transcranial magnetic stimulations (TMSs) and proposing a shielding system composed of an aluminum half cylinder placed around the coil. The analysis is carried out through a finite-element approach, using the Duke (Virtual Family) anatomical model to represent the operator body. The TMS apparatus, a spiral circular coil supplied by a short-duration sinusoidal current of ~6 kA, has been analyzed with and without shield. The 60 relative positions of the coil with respect to the TMS operator body have been considered, involving distance, orientation angle, and vertical height. The results show that the operator exposure exceeds the basic restrictions suggested by the Guidelines of the International Commission on Non-Ionizing Radiation Protection, when the distance from the coil decreases below 64 cm, but the minimal distance is reduced to 38 cm by the conductive shield. Moreover, the staff exposure reduces when the coil overlooks the operator head, while it worsens as the position of the coil descends at the height of shoulders and chest.